(untitled) (ENTHYMEMA, 2009)
During the opening lecture of his course at Collège de France, held on April 6th 2006, Thomas Pavel talks about the emotional and ethical aspects of reading and about «completely surrending» to literature. How is everyday life transfigured into poetic invention? How is our ego identified in the literary work? The scholar traces the origin of this process to the radically different principles governing ego and life. Because of this, the reader is able to grasp and understand the real meaning of the book. This, however, is never completely revealed in a clear way. Instead, it becomes the object of a never-ending dialogue among the readers: it is therefore their care the meaning is entrusted to.